Internet cognitive–behavioural treatment for panic disorder: randomised controlled trial and evidence of effectiveness in primary care. Issue 2 (March 2016) - Allen, Adrian R.; Newby, Jill M.; Mackenzie, Anna; Smith, Jessica; Boulton, Matthew; Loughnan, Siobhan A.; Andrews, Gavin
Abstract : Background: Internet cognitive–behavioural therapy (iCBT) for panic disorder of up to 10 lessons is well established. The utility of briefer programmes is unknown. Aims: To determine the efficacy and effectiveness of a five-lesson iCBT programme for panic disorder. Method: Study 1 (efficacy): Randomised controlled trial comparing active iCBT ( n =27) and waiting list control participants ( n =36) on measures of panic severity and comorbid symptoms. Study 2 (effectiveness): 330 primary care patients completed the iCBT programme under the supervision of primary care practitioners. Results: iCBT was significantly more effective than waiting list control in reducing panic ( g =0.97, 95% CI 0.34 to 1.61), distress ( g =0.92, 95% CI 0.28 to 1.55), disability ( g =0.81, 95% CI 0.19 to 1.44) and depression ( g =0.79, 95% CI 0.17 to 1.41), and gains were maintained at 3 months post-treatment (iCBT group). iCBT remained effective in primary care, but lower completion rates were found (56.1% in study 2 v. 63% in study 1). Adherence appeared to be related to therapist contact. Conclusions: The five-lesson Panic Program has utility for treating panic disorder, which translates to primary care. Adherence may be enhanced with therapist contact.